2017
DOI: 10.5606/archrheumatol.2017.6078
|View full text |Cite
|
Sign up to set email alerts
|

Presarcopenia and its Impact on Disability in Female Patients With Rheumatoid Arthritis

Abstract: Objectives:This cross-sectional pilot study aims to investigate presarcopenia in female patients with rheumatoid arthritis (RA) and to evaluate its relationship to the disability assessment. Patients and methods: Forty female patients with RA (mean age 48.3±8.3; range 31 to 66 years) and 40 healthy controls (mean age 46.2±6.9; range 31 to 58 years) matched for age, sex, and body mass index were included. Pain, morning stiffness duration, disease activity score, erythrocyte sedimentation rate, C-reactive protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
4
10
0
1
Order By: Relevance
“…Torii et al (12) described a higher prevalence of low muscle mass in RA patients (49%) in Japan, and similar findings were also found by two independent studies performed in RA patients from Morocco and Turkey (39.8% and 43.3%, respectively) (13,8). However, the rate of low skeletal muscle mass observed in our patients with RA was lower (27.8%), closer to that found in studies performed in Europe and in the United States, in which the reported rates of low muscle mass vary from 20% to 28.6% (7,10). An even lower prevalence of low muscle mass in RA has been reported in two additional studies, one of which was performed in Spain and the second of which was reported in the United States (13% and 11%, respectively) (9, 11).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Torii et al (12) described a higher prevalence of low muscle mass in RA patients (49%) in Japan, and similar findings were also found by two independent studies performed in RA patients from Morocco and Turkey (39.8% and 43.3%, respectively) (13,8). However, the rate of low skeletal muscle mass observed in our patients with RA was lower (27.8%), closer to that found in studies performed in Europe and in the United States, in which the reported rates of low muscle mass vary from 20% to 28.6% (7,10). An even lower prevalence of low muscle mass in RA has been reported in two additional studies, one of which was performed in Spain and the second of which was reported in the United States (13% and 11%, respectively) (9, 11).…”
Section: Discussionsupporting
confidence: 87%
“…Our findings of a higher prevalence of low muscle mass in women with RA compared with controls are consistent with the data reported by other case-control studies. A similar result was identified by Alkan et al in Turkey with a rate of low muscle mass of 20% in their patients with RA versus 7% in their controls(7).Several studies have also compared the frequency of low skeletal muscle mass in RA patients with controls (6, 8-10). Delgado-Frias et al in Spain described a frequency of low muscle mass of 13% in RA patients compared to 6% in controls (9), whereas Tournadre et al in France identified a frequency of low muscle mass of 28.6% in RA patients but only in 4.8% in their controls(10).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The diagnosis of sarcopenia was performed in the presence of both muscle mass and muscle strength reduction, while muscle mass reduction alone without muscle strength impairment was considered presarcopenia [1,18]. The reference values for the diagnosis of muscle mass and muscle strength reduction were: MMI < 6.75 kg/m 2 in women and <10.75 kg/m 2 in men (associated with physical disability in subjects aged ≥60 years) and handgrip strength <20 kg in women and <30 kg in men (associated to reduced mobility), respectively [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Older people can be classified into three stages: robust, pre-sarcopenia (i.e., decrease in muscle mass, but not in gait speed or grip strength), and sarcopenia. Pre-sarcopenia is the stage of shift from robust to sarcopenia [20]. Previous studies have shown that people who are not considered to have sarcopenia because of preserved grip strength also have an increased risk for adverse outcomes [2].…”
Section: Introductionmentioning
confidence: 99%